Cell spreading and viability on single-walled carbon nanotube/zinc oxide nanowire heterostructures synthesized by chemical vapor deposition - Luc, Emily; Aziz, Bashar; Kim, Yoosuk; Lespasio, Marcus; Jombo, Philomena; Zustiak, Silviya P.; Kuljanishvili, Irma (Frontiers in Carbon, 2024)
Recent studies have shown the wide array of biomedical applications for nanomaterials such as singlewalled carbon nanotubes (SWCNTs) and zinc oxide nanowires (ZnO NWs). SWCNTs are noncytotoxic and have a varying range of mechanical, physical, and electrical properties useful to biomedical research. ZnO NWs are biocompatible, antibacterial, and exhibit piezoelectric properties that could stimulate cell growth. While recent research has been conducted using these nanomaterials independently, our study is focused on testing cell behaviors when seeded on SWCNTs, ZnO NWs and their heterostructure assemblies. ZnO NWs/SWCNTs heterostructures prepared via chemical vapor deposition (CVD) have not been used in biomedical applications to date. Here, we describe fabrication and characterization of the two nanomaterials independently and in a heterostructure formation. The NIH 3T3 fibroblast cells and U87 glioblastoma cells were seeded on all samples, including SiO2/Si control/reference samples, and the cell growth was studied via fluorescence microscopy and scanning electron microscopy. The focus of this study was to evaluate cell spreading, filopodia extensions, and cell viability on these nanomaterial assemblies. Results indicated that cells were able to extend filopodia on all nanostructures, however cell spreading was more pronounced on SWCNTs, and cell viability was compromised on the ZnO NWs and the ZnO NWs/SWCNTs heterostructures. In addition, soluble compounds from the nanomaterials were tested to determine their cytotoxicity towards both NIH 3T3 and U87 cells. Results indicated a significant decrease in filopodia length, cell spreading, and cell viability when cells were exposed to ZnO NWs-conditioned cell media. These findings on cellular behavior involving SWCNTs, ZnO NWs, and ZnO NWs/SWCNTs heterostructure provide valuable information on the suitability of SWCNTs and ZnO NWs for future uses in biomedical applications.